2012
DOI: 10.2134/agronj2012.0213
|View full text |Cite
|
Sign up to set email alerts
|

Planting Date and Harvest Maturity Impact on Biofuel Feedstock Productivity and Quality of Sweet Sorghum Grown under Temperate Louisiana Conditions

Abstract: Sweet sorghum [Sorghum bicolor (L.) Moench] is recognized as a promising biomass energy crop for meeting the increasing demand for bioenergy feedstocks. Field experiments were conducted at sites in northern and southern Louisiana for 2 yr to assess planting date and harvest maturity effects on yield from primary plantings and ratoon crops. The cultivar M81‐E was evaluated using a split plot arrangement of treatments in randomized complete block designs. Planting date from mid‐March to early July was the primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…Conservation tillage increased biomass by 11 % during the dry year, but no difference was observed between tillage systems for the wet year [36]. In the Southeast, sweet and photoperiod sensitive sorghums have been examined as potential energy crops due to high biomass production, low N requirements, and drought tolerance relative to corn [34,[36][37][38]. Sweet sorghum has additional benefits of a typically shorter growing season and production of fermentable sugars, although biomass production is reduced compared to photoperiod sensitive sorghum [34,38].…”
Section: Annual Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservation tillage increased biomass by 11 % during the dry year, but no difference was observed between tillage systems for the wet year [36]. In the Southeast, sweet and photoperiod sensitive sorghums have been examined as potential energy crops due to high biomass production, low N requirements, and drought tolerance relative to corn [34,[36][37][38]. Sweet sorghum has additional benefits of a typically shorter growing season and production of fermentable sugars, although biomass production is reduced compared to photoperiod sensitive sorghum [34,38].…”
Section: Annual Cropsmentioning
confidence: 99%
“…In the Southeast, sweet and photoperiod sensitive sorghums have been examined as potential energy crops due to high biomass production, low N requirements, and drought tolerance relative to corn [34,[36][37][38]. Sweet sorghum has additional benefits of a typically shorter growing season and production of fermentable sugars, although biomass production is reduced compared to photoperiod sensitive sorghum [34,38]. In addition to the bmr gene, low amylose or waxy endosperm genes and sweet genes are being incorporated and evaluated in current breeding programs that would improve sorghum as a bioenergy feedstock [39].…”
Section: Annual Cropsmentioning
confidence: 99%
“…Both photoperiod and temperature interact, thus further influencing yield especially for very late plantings (Rao et al, 2013). Much information on the impact of planting date on stalk and sugar yields are available on sweet sorghum genotypes grown in temperate climatic conditions (Han et al, 2012;Burks et al, 2013), but information is very limited on mid-summer planting on ethanol production. The present experiment was conducted to identify optimum time of sowing and N level for achieving higher biomass and grain yield for ethanol production.…”
Section: Introductionmentioning
confidence: 99%
“…Lower productivity in ratoon crops has been previously shown to be caused by unavoidable damage during harvest (e.g. in sugarcane (Bull, 2000;Cabral et al, 2012) and in sorghum (Han et al, 2012;Rao et al, 2013). It has also been reported that certain sorghum genotypes exhibit lower biomass production in the second and third ratoon crop of the growing season compared to the crop grown from seed (Rooney et al, 2007;Rao et al, 2013), however, these genetic drivers are not well resolved.…”
mentioning
confidence: 99%